Thirty years of the convention on the rights of the child: Developments in child sexual abuse and exploitation. (December 2020) - Simon, June; Luetzow, Ann; Conte, Jon R.
Abstract: Since its adoption by the United Nations in November 1989, the Convention on the Rights of the Child (CRC) has become the most universally ratified human rights treaty in history; presently only the United States has not ratified it. The CRC articulates children's human rights and notably includes freedom from sexual abuse and exploitation. Yet thirty years after the Convention was adopted, child sexual abuse and exploitation (CSA/E) remain serious, persistent, and evolving global issues. This overview both describes the current state of research on child sexual abuse and exploitation and evaluates the CRC's legacy in terms of State-level responses to CSA/E. Points of agreement and disagreement over what constitutes CSA/E and how widespread it is are explored. Also presented are the contexts in which CSA/E takes place, and factors associated with children's risk of being sexually abused or exploited. Emerging issues in these areas are the internet and children's use of it, as children may now become subject to abuse or exploitation even when physically alone. The second part of the paper addresses the CRC's influence on States' domestic legislation and States' responses to CSA/E more broadly. Gaps in efforts to monitor and report on the CRC's implementation with respect to its impact on CSA/E are described. The discussion offers guidance for future efforts to research and respond to child sexual abuse and exploitation, and in particular the ongoing need for support to survivors beyond the legal response paradigm.